2012
DOI: 10.1108/07363761211193019
|View full text |Cite
|
Sign up to set email alerts
|

A market segmentation approach to esteem and efficacy in information search

Abstract: Purpose -Building on consumer purchase behavior and self-confidence theories combined with insights from marketing segmentation literature, this study aims to investigate the influence of self-esteem and self-efficacy on consumers' selection of sources of information when making a product buying decision. Design/methodology/approach -Multivariate analysis of variance was used to analyze the main and interaction effects of the independent categorical variables on multiple dependent interval variables. An online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Taking this into account, it is suggested that, in general, the marketing communication should emphasise the feeling of self-confidence and perceived effectiveness of consumers with greater perceived category knowledge. Exposure to impersonal advertisingfor instance on the Internetis an effective way of reinforcing subjective knowledge for selfconfident people (Bishop and Barber, 2012). In a context of purchasing in hypermarkets, these consumers may also be receptive to marketing actions that promote opportunities for knowledge development.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taking this into account, it is suggested that, in general, the marketing communication should emphasise the feeling of self-confidence and perceived effectiveness of consumers with greater perceived category knowledge. Exposure to impersonal advertisingfor instance on the Internetis an effective way of reinforcing subjective knowledge for selfconfident people (Bishop and Barber, 2012). In a context of purchasing in hypermarkets, these consumers may also be receptive to marketing actions that promote opportunities for knowledge development.…”
Section: Resultsmentioning
confidence: 99%
“…The process of choosing wine is complex, namely, due to the product breadth, to market differentiation, and to the considerable information asymmetry. Being an experience good, the consumers' knowledge plays a key role in the decision process (Bishop and Barber, 2012) and the information processing ends up being an intense experience in wine acquisition (Bruwer et al, 2011). To overcome this situation of complexity, the buyer will retrieve his/her own life experiences, knowledge and the most diverse sources of external information.…”
Section: Literature Review Subjective Knowledge and Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumers with high self‐confidence are likely to assess themselves as having high product knowledge (Bearden et al, ). Information acquisition confidence implies that consumers are aware of the different information parameters and sources while searching for product information (Bishop & Barber, ; Mourali, Laroche, & Pons, ). This confidence can be the result of the ongoing search regarding the product that probably increases their knowledge.…”
Section: Theoretical Foundationsmentioning
confidence: 99%